Genetic instability at the adenine phosphoribosyltransferase locus in mouse L cells. - Tischfield, J A (1982)
Resistance to adenine analogs such as 2,6-diaminopurine occurs at a rate of approximately 10(-3) per cell per generation in mouse L cells. This resistance is associated with a loss of detectable adenine phosphoribosyltransferase activity. Other genetic loci in L cells have the expected mutation frequency (approximately 10(-6)). Transformation of L cell mutants with Chinese hamster ovary cell DNA results in transformants with adenine phosphoribosyltransferase activity characteristic of Chinese hamster ovary cells. No activation of the mouse gene occurs on hybridization with human fibroblasts. That this high frequency event is the result of mutation rather than an epigenetic event is supported by antigenic and reversion studies of the 2,6-diaminopurine-resistant clones. These results are consistent with either a mutational hot-spot, a locus specific mutator gene, or a site of integration of an insertion sequence.